Why pluralism. (23rd November 2022) - Jr., Frederic B. Jennings
This paper makes a case for pluralism in academics, arguing that dogma is a pathological symptom of a model based on substitution applied in a setting characterised by complementary interactions, such as those in education, ecology or in all long-term economics. Our rational limits make all of our knowledge selective, focused and therefore also implacably blind to what is ignored, implying a case for multiple models since each provides some perspective on all left out of the others. The more ways we can think about something, the better our chance of fitting our frame to the case at hand. Here, we consider the issue in a historical context: the general use of substitution assumptions in economics stems from a claim about decreasing returns that does not pertain to long-run cases, which involve falling costs and therewith a generalised complementarity in economic relations. A use of competitive frames in complementary environments simply undermines output and effort, as well as shortens our planning horizons, creating a myopic culture in self-destruct mode. What is required in these situations is a shift to cooperation, which will open our minds to new vistas.